Adaptation of Betawi Traditional Music Performers to Preserve Their Existence in a New Normal Era - Wardhana, Iwan Henry; Permana, Cecep Eka; Puspitasari, Maria; Chotib (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research explored an adaptation to survive in the new normal era in the Jakarta art performers in general and the Betawi traditional music performers in particular. The implementation of social restrictions and regional quarantines in Jakarta had prevented many sectors from making economic activities, including Betawi traditional music performers. The research examined how the Betawi traditional music performers in the Betawi Cultural Village of Setu Babakan adapted to health protocols on stage performance and internet knowledge on virtual performances in the new normal era. Data are taken from in-depth interviews and classified to determine the adaptation ability carried out by Betawi traditional music performers. The Betawi traditional music performance studios were Sanggar Arrominia, Sanggar Gambang Kromong Setia Muda, and Sanggar At-Taubah with certain types of traditional music, such as Gambus, Samrah, Qasidah, Hadrah, and Gambang Kromong. It is found that during the social restriction and regional quarantine in Jakarta, the studios experience a decrease in their request to perform. They need to survive by adapting to the new normal era through the application of the health protocols on stage performance and exploring their knowledge on the internet to conduct the virtual performance. The health protocol limits the flexibility in performing traditional music through mask and face-shield wearing. The average knowledge of the internet and having limited internet devices are some other situations to be adapted by traditional music performers. The adaptation needs to be carried out sometime in the future, and this pandemic only accelerates the need.